Climate change: lived experience, policy and public action. Issue 1 (11th March 2014) - Abbott, Dina; Wilson, Gordon
Abstract : Purpose: – The purpose of this paper is to explore the importance of lived experiences, as complementary knowledge to that provided by the sciences, for policy and intervention on climate change. Design/methodology/approach: – This conceptual paper draws on several strands within the context of climate change: knowledge and power; human engagement; the meaning of "lived experience" (and its association with "local/indigenous knowledge"); its capture through interdisciplinary and transdisciplinary inquiry; post-normal science; rationalist and public action approaches to policy and intervention. The paper combines these strands from their different literatures, previous work by the authors and interdisciplinary deliberation in a European climate change education project. Findings: – The case is made for taking account of lived experiences in climate change policy and intervention, and the dangers of not doing so. The paper, however, also identifies the challenge of establishing the validity of lived experience alongside forms of scientifically derived knowledge, and the practical challenge of capturing it in a form that is accessible to practitioners. It concludes by arguing that a public action approach to policy provides a better lens than the conventional rationalist approach to analyse the contested nature of climate science and the potential of lived experience to inform debates through active engagement. Research limitations/implications: – There has been no empirical study on climate change that addresses the research concerns. This would be necessary to forward the paper's agenda. Practical implications: – The paper makes a case for formalising evidence that is based on lived experience in policy making and intervention, and the approach that is needed. Originality/value: – The work develops the concept of lived experience in the context of climate change. Its public action theory of knowledge provides a novel means of analysing and meeting the challenge of diverse knowledge on climate change.